Scapular Muscle Tests in Subjects With Shoulder Pain and Functional Loss: Reliability and Construct Validity - Michener, Lori A; Boardman, N Douglas; Pidcoe, Peter E; Frith, Angela M (Physical therapy, 2005)
Background and Purpose. Scapular muscle performance evaluated with a handheld dynamometer (HHD) has been investigated only in people without shoulder dysfunction for test-retest reliability of data obtained with a single scapular muscle test. The purpose of this study was to assess the reliability, error, and validity of data obtained with an HHD for 4 scapular muscle tests in subjects with shoulder pain and functional loss. Subjects and Methods. Subjects (N=40) with shoulder pain and functional loss were tested bymeasuring the kilograms applied with an HHD during 3 trials for muscle tests for the lower trapezius, upper trapezius, middle trapezius, and serratus anterior muscles. Concurrently, surface electromyography (sEMG) data were collected for the 4 muscles. The same procedures were performed 24 to 72 hours after the initial testing by the same tester. Muscle tests were performed 3 times, and the results were averaged for data analysis. Results. Intraclass correlation coefficients for intratester reliability of measurements of isometricforce obtained using an HHD ranged from .89 to .96. The standard error of the measure (90% confidenceinterval [CI]) ranged from 1.3 to 2.7 kg; the minimal detectable change (90% CI) ranged from 1.8 to 3.6 kg. Construct validity assessment, done by comparing the amounts of isometric muscle activity (sEMG) for each muscle across the 4 muscle tests, revealed that the muscle activity of the upper trapezius and lower trapezius muscles washighest during their respective tests. Conversely, the isometric muscle activity of the middle trapezius and serratus anterior muscles was not highest during their respective tests. Discussion and Conclusion. In people with shoulder pain and functional loss, the intrarater reliability and error over 1 to 3 days were established using an HHD for measurement of isometric force for the assessment of scapular muscle performance. Error values can be used to make decisions regarding individual patients. Construct validity was established for the lower and upper trapezius muscle tests; therefore, these tests are advocated for use. However, construct validity was not demonstrated for the serratus anterior and middle trapezius muscle tests as performed in this study. Further investigation of these muscle tests is warranted.